How the Relationship between Corporate Governance and Foreign Portfolio Investment Expediate Supply Chain Growth in Indonesia? - Sinaga, Obsatar; Kartadjumena, Eriana; Sukmawati, Fitri; Jayaatmaja, Muhamad Alan; Ahmad Razimi, Mohd Shahril Bin (International Journal of Supply Chain Management, 2019)
Objective of the study is to examine the role of corporate governance in nationwide supply chain growth through foreign portfolio investment (FPI). FPI is considered as mediating variable between corporate governance and apply chain growth. To approach the objective of this study, primary data were collected and analysed through statistical software. Data were collected from Indonesian economists. Total number of three hundred questionnaires were used in this process. After data collection, it was analysed with the help of PLS. Findings of the study highlighted that corporate governance has important role in FPI and supply chain growth. Any fluctuation in corporate governance has direct impact on FPI and supply chain growth. Corporate governance leads to FPI and FPI leads to supply chain growth. The study is beneficial for Indonesian supply chain companies while making the strategies.